2021
DOI: 10.1002/anbr.202000082
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity, Biodistribution, and Pharmacokinetics Studies of Pegylated Platinum Nanoparticles in Mouse Model

Abstract: Pegylated colloidal platinum nanoparticles (PEG‐PtNPs) are widely used as a potential agent for diagnosis and therapy of various diseases including cancer. Prior to any preclinical applications, detailed investigations of toxicity, biodistribution, clearance, and pharmacokinetics (PKs) of new nanomaterials are essential. Extensive toxicological studies of PEG‐PtNPs are not reported in a systematic manner elsewhere. Herein, acute toxicity of PEG‐PtNPs is thoroughly investigated in mouse model. Prior to study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…In contrast, the administration of higher doses at 50 mg kg À1 indicated a remarkable toxicity. 40 Finally, histopathological analyses at tissue level revealed no major reactive changes (such as vascular, degenerative, inflammatory, or hyperplastic changes) in the control group and in the group dosed with Pt NPs at 10 mg kg À1 . However, mice treated with 50 mg kg À1 PVP-Pt NPs exhibited significant nephrotoxicity and inflammation in the brain.…”
Section: In Vivo Experiments With Pt Npsmentioning
confidence: 87%
See 3 more Smart Citations
“…In contrast, the administration of higher doses at 50 mg kg À1 indicated a remarkable toxicity. 40 Finally, histopathological analyses at tissue level revealed no major reactive changes (such as vascular, degenerative, inflammatory, or hyperplastic changes) in the control group and in the group dosed with Pt NPs at 10 mg kg À1 . However, mice treated with 50 mg kg À1 PVP-Pt NPs exhibited significant nephrotoxicity and inflammation in the brain.…”
Section: In Vivo Experiments With Pt Npsmentioning
confidence: 87%
“…However, mice treated with 50 mg kg À1 PVP-Pt NPs exhibited significant nephrotoxicity and inflammation in the brain. 40 The PKs studies in the same work 40 indicated that after injection of 10 mg kg À1 dose, the time required to reach maximum levels of Pt NPs in blood plasma was 1 h and time for clearance at 50% in the plasma reached to 135 hours. The biodistribution studies showed the deposition of excess of Pt NPs in major organs such as liver, heart, lungs or kidney.…”
Section: In Vivo Experiments With Pt Npsmentioning
confidence: 96%
See 2 more Smart Citations
“…These features have the potential to circumvent some drawbacks of conventional pharmaceuticals, such as unfavorable side effects, imperfect selectivity, and undesirable pharmacokinetics. Some current efforts were done to synthesize more biocompatible platinum nanoparticles which are hemocompatible ( Mukherjee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%